Understanding the role of the principal in managing cultural diversity among educators. - Kistadoo, Lawrence Philips (My University, 2009)
The first democratic elections in South Africa in 1994 gave birth to a ‘new’ nation which changed every sector of the country. The separate education systems and departments created under apartheid were dismantled and integrated into a single national education framework. This meant that people from different races, cultures and backgrounds began working together in an attempt to bring about a single, unified nation. The new democratic government introduced legislation such as the South African Schools Act of 1996 (SASA) and the Employment Equity Act of 1998. These acts were to introduce transformation and ensure that institutions employed an equitable distribution of staff which reflected the demographics of the community and the nation as a whole. The issues and challenges arising from this meant that school leaders needed additional skills in managing a diverse workforce made up of a melting pot of cultures. This study examines the role of school principals in managing educators in a culturally diverse school environment. It explores the different leadership styles adopted by principals. In South Africa schools have become increasingly diverse in terms of race, language and religion. School principals are therefore faced with huge challenges in dealing with these differences among their staff. The research focuses on a few of the areas of contestation in schools whilst acknowledging that diversity involves a wide range of issues in schools. This is inevitable when there is a melting pot of cultures, races, languages and religions. In order to ensure that a high standard of education is maintained in their institutions, school principals need to understand how people from the diverse cultures present in the school interact, and how they, as managers and leaders, could achieve integration or synergy amongst all staff members. An attempt is also made to provide clarity on the meanings of the concepts of culture and diversity, how it influences an individual, and also how an understanding of these concepts could affect principals’ leadership and management styles. iii The qualitative research methods that were used involved a small scale case study which included questionnaires and structured interviews to follow up and probe responses from the principal and educators of a school in Johannesburg. A school, which reflects diversity amongst their staff members, was selected for this research. The school selected had initially been an advantaged, whites-only suburban school. The changes in demographics in recent years, and the affordability of homes in the southern suburbs of Johannesburg, gave rise to an increase in the social movement of the black middleclass into the area around the school. This resulted in an influx of black, coloured and Indian families from outlying townships and informal settlements, making this community a prime example of diverse cultures living together. After South Africa’s democratisation in the mid nineties, recruitment of staff and learners from different race, language and religious groups began rapidly to increase and be accepted at this school. The school’s profile is illustrated in the form of graphs (see chapter 5), which shows its staff composition prior to 1994 and the changes experienced since then. The responses of the principal and educators have also been analysed with regard to their understanding of diversity; the integration of staff; the benefits to the school in becoming diverse; and the role and competencies of the principal in managing a diverse cultural environment. The research methodology used was interpretive and endeavoured to make sense of the principal’s management style in managing cultural diversity. The research was also based on a study of the literature, which attempted to show the extent to which effective management of cultural diversity by principals was taking place. The literature review and the research into this area highlight the issues affecting diverse, multicultural environments as well as some practices and beliefs of the different cultural groups themselves. An attempt was also made to find out to what extent schools were successful with positive racial integration and relations (including language and religion). How the literature supports or provides alternate views to this case study forms a critical component of the research. The findings of this research, as demonstrated through the iv case study and corroborated through the literature study, show that a democratic, participatory and consultative management style by school principals, as opposed to an autocratic/bureaucratic management style, is crucial in managing staff diversity.